2016
DOI: 10.1556/2050.2016.0001
|View full text |Cite
|
Sign up to set email alerts
|

The validity and structure of mating intelligence

Abstract: Abstract. Mating Intelligence (MI) is a hypothesized constellation of mental adaptations that generate adaptive strategies in human mating (Geher & Miller, 2008). Although past research has theoretically explored and empirically evaluated the construct, using a MI scale that was borne of the ideas from Geher and Miller's work, this study seeks further understanding of this construct by demonstrating incremental validity. Two studies, each with large samples, demonstrate that MI predicts important outcomes beyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…Also, the reliability coefficients for all factors and the total questionnaire in both samples (except self-deception subscale in the female sample) were higher than 0.70, which indicates the appropriate reliability. The results are in line with studies that examine the validity and reliability of this scale (Geher et al, 2016;O'Brien et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Also, the reliability coefficients for all factors and the total questionnaire in both samples (except self-deception subscale in the female sample) were higher than 0.70, which indicates the appropriate reliability. The results are in line with studies that examine the validity and reliability of this scale (Geher et al, 2016;O'Brien et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Psychometric characteristics of this scale are well-documented in some earlier studies. Geher et al (2016) confirmed the validity of this scale using exploratory factor analysis (EFA) in a sample of 1,200 men and women. They reported the reliability for men and women versions, 0.76 and 0.55, respectively.…”
Section: Measuresupporting
confidence: 53%
See 3 more Smart Citations